The impact of the question network strategy in accordance with mental capacity in the strength of cognitive control in the subject of teaching methods of sports education for undergraduate students - جنان غازي صكر أ.م.د.نجلاء عباس الزهيري (الرياضة المعاصرة)
The study aimed at identifying the mental capacity of the research sample and classifying them for the purposes of the study, preparing the scale of cognitive control of the subject of teaching methods of sports education, preparing educational units by establishing the question network for the subject of the teaching methods of sports education, and adopting the experimental method by experimental design workers (2×2) for the two groups The limits of the research community are represented by third-stage students of the Department of Physical Education and Sports Science in the morning study of the College of Knowledge, the Community University, which continues in the regular working hours of the year (2019-2020) adult Their number (150) students and the requirements of study in the preparation of measuring instruments, selected three groups (sample construction and statistical analysis) (80 students), survey (10) students, and (60) students for the main sample classified by the mental capacity scale to the two pilots studied from them With the strategy of the network of questions, and the two officers in the manner followed, the researchers prepared the measure of the power of cognitive control with systematic sequential steps and many statistical treatments to be suitable for her eye, and then prepared an educational curriculum for the theoretical subject by which students study in the classroom and an application plan for this method taught students in The sports hall at the rate of two units per week and each one unit to receive students teaching strategically network questions (6) theoretical units, and after the completion of the preparation and construction of measuring tools and the study experience the researcher verified the results using the statistical bag system (SPSS-V26) to be Conclusions and applications that the scale of cognitive control is a valid tool for measuring students of the third stage of the Department of Physical Education to achieve scientific requirements according to the parameters of measurement and evaluation, and apply a strategy The network of questions in teaching the teaching methods of teaching physical education teaching helps students who study in it to improve the level of cognitive control power, and their superiority by improving this subject on students studying this subject with the methods used in the lesson, and that the strategy of the question network is more appropriate with students with a high level of mental capacity in improving the level of cognitive control, and takes into account students with a low level of mental capacity in this improvement, and it is necessary to take into account the differences of individual students at the level of capacity when improving cognitive control in teaching The subject of teaching methods of teaching physical education.